Filipino Child Health in the United States: Do Health and Health Care Disparities Exist? - Joyce R. Javier, MD, MPH; Lynne C. Huffman, MD; Fernando S. Mendoza, MD, MPH (Centers for Disease Control and Prevention, 2007)
IntroductionFilipinos are the second largest Asian subgroup in the United States, but few studies have examined health and health care disparities in Filipino children. The objectives of this review are 1) to appraise current knowledge of Filipino children's health and health care and 2) to present the implications of these findings for research, clinical care, and policy.MethodsWe identified articles for review primarily via a Medline search emphasizing the terms Filipino and United States crossed with specific topics in child and adolescent health that fall under one of Healthy People 2010's 28 focus areas. ResultsFilipino children are underrepresented in medical research. Studies that compare Filipino children and adolescents with white children or children of other Asian Pacific Islander subgroups suggest disparities with regard to gestational diabetes, rates of neonatal mortality and low birth weight, malnutrition in young children, overweight, physical inactivity and fitness, tuberculosis, dental caries, and substance abuse. Studies that compare Filipino adults with white adults describe adult Filipino health problems similar to those of Filipino children, including higher rates of diabetes, hypertension, and metabolic syndrome. Health care disparities remain to be determined.ConclusionHealth and health care disparities appear to exist for Filipino children, but more research is needed to confirm these findings. Practitioners serving this population need to consider social and cultural factors that can increase or diminish risk for health problems. There are priorities in research and policy that, if pursued, may improve the health care and health outcomes of Filipino children.